2014
DOI: 10.1111/jdi.12307
|View full text |Cite
|
Sign up to set email alerts
|

High‐normal urinary albumin‐to‐creatinine ratio is independently associated with metabolic syndrome in Chinese patients with type 2 diabetes mellitus: A cross‐sectional community‐based study

Abstract: Aims/IntroductionMicroalbuminuria is positively related to metabolic syndrome (MetS). Our aim was to investigate whether urinary albumin-to-creatinine ratio (UACR) within the normal range is independently associated with MetS in Chinese community-based patients with type 2 diabetes.Materials and MethodsA total of 514 participants (206 males and 308 females; mean age 66 years) with UACR less than 3.5 mg/mmol were enrolled from two downtown areas of Shanghai. The participants were stratified into quartiles accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…In present study we further examined the association between elevated 24 h UAE and risk of MetS by dividing participants into four groups according to quartiles of 24 h UAE within normal range. Our study indicated that the odds of MetS significantly increased with increase of 24 h UAE within normal range, which is in agreement with the findings of previous studies[ 3 , 7 9 ]. To date, only one prospective cohort study has attempted to determine the association between urine albumin-to-creatinine ratio (UACR) estimated by a single morning urine sample and the development of MetS, which reported that compared with participants with first tertile of UACR, the hazard ratios (HRs) and 95% confidence intervals (CI) for MetS was 1.01 (0.71–1.45) and 1.57 (1.14–2.18) for participants in the second and third tertiles, respectively[ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…In present study we further examined the association between elevated 24 h UAE and risk of MetS by dividing participants into four groups according to quartiles of 24 h UAE within normal range. Our study indicated that the odds of MetS significantly increased with increase of 24 h UAE within normal range, which is in agreement with the findings of previous studies[ 3 , 7 9 ]. To date, only one prospective cohort study has attempted to determine the association between urine albumin-to-creatinine ratio (UACR) estimated by a single morning urine sample and the development of MetS, which reported that compared with participants with first tertile of UACR, the hazard ratios (HRs) and 95% confidence intervals (CI) for MetS was 1.01 (0.71–1.45) and 1.57 (1.14–2.18) for participants in the second and third tertiles, respectively[ 7 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study further showed that the prevalence of MetS gradually increased with increasing normal-range 24-hour UAE quartiles, which is consistent with previous studies 15 26–28. Thus far, only one prospective cohort study reported HRs with 95% CIs for MetS: 1.57 (95% CI 1.14 to 2.18) for the three highest albumin:creatinine ratio quartiles compared with the lowest one 28.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of MAU increased significantly with increasing numbers of MetS components after the subjects were divided by the number of MetS components. The same results were obtained in previous studies 12–15 25 26. This finding indicates that a large number of participants with MAU are easily overlooked in routine health examinations that do not include MAU measurements.…”
Section: Discussionsupporting
confidence: 88%
“…Weight, height, waist circumference, hip circumference, and blood pressure were conducted for individuals by the prior protocols [1012, 23, 28]. Body mass index (BMI) was measured as the ratio of the weight to the height squared.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, metabolic syndrome (MetS), comprised of impaired glucose regulation, HTN, dyslipidemia, and central obesity, existed in approximately two-thirds of type 2 diabetic patients or more [22]. Our previous reports also found more MetS in type 2 diabetes [23]. Both the PROSPER study and BRHS study indicated that MetS and its components were related to type 2 diabetes [24].…”
Section: Introductionmentioning
confidence: 99%